Associations of serum soluble Fas and Fas ligand (FasL) with outcomes in systemic lupus erythematosus. Issue 1 (15th June 2020) - Vincent, Fabien B; Kandane-Rathnayake, Rangi; Koelmeyer, Rachel; Harris, James; Hoi, Alberta Y; Mackay, Fabienne; Morand, Eric F
Abstract : Objective: Fas/Fas ligand (FasL) and B cell-activating factor (BAFF) signalling have pivotal roles in SLE pathogenesis. We investigated the clinical associations of serum concentrations of soluble Fas (sFas) and soluble FasL (sFasL) in SLE and their relationship with BAFF. Methods: Serum sFas and sFasL were quantified by multiplex assay, and BAFF by ELISA, in 118 patients with SLE and 17 healthy controls (HC). SLE disease activity and organ damage were assessed using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) and the Systemic Lupus International Collaborating Clinics Damage Index. Results: sFas, sFasL and BAFF were detectable in all samples. Serum sFas and sFasL were significantly higher in SLE compared with HC. In univariable regression analyses, patients with active renal disease and those with flare had significantly higher levels of sFas compared with those without. High serum BAFF in patients with SLE was associated with increased sFas but not sFasL. The association between sFas and renal disease remained significant after adjusting for BAFF, but the association with flare attenuated. High sFas levels were associated with increased time-adjusted mean SLEDAI-2K, even after adjusting for BAFF, and with higher odds of flare over time. In contrast, high sFasL was associated with reduced organ damage over time. Serum sFasL/sFas ratio was negatively associated with active overall disease, flare and organ damage. Conclusions: Serum sFas is associated with active renal SLE, and active disease and flare over time, while sFasL/sFas ratio is negatively associated with disease activity and organ damage accrual. Treatments correcting abnormal levels of sFas/FasL may be worthy of evaluation in SLE.